A Historical Review of the Books of Proofs of Prophecy in the Art of Seerah Writing - Dr. Asma Aziz; Dr. Asma Aziz (jihat-ul-islam, 2023)
Art of Seerah Writings of Hazrat Muhammad (SAWW) has a vast range of areas. Among them Dalail un Nabwwah is one of unique sub-field of Seerah writings that debates on the evidences of Prophecy of Hazarat Muhammad (SAWW). This research aims to review historically all the literature that wrote on this subject. The denial of the Prophethood of Hazrat Muhammad by the non Muslim was the big challenge for Muslim Scholars. This literature was written to reply the nonMuslims on their objections and for the Muslim to acknowledge the status of Prophecy of Hazrat Muhammad (SAWW) and to increase the love towards him (SAWW). In the development of this literature, it was written in Arabic Language and the Arab Autobiographers took part in this area of the Seerah. And later on their work and researches were transformed in other languages of the world.